Influence of Al additions in Zn–based filler metals on laser welding–brazing of Al/steel. (August 2018) - Tan, Caiwang; Zang, Chengwei; Xia, Hongbo; Zhao, Xiaoye; Zhang, Kaiping; Meng, Shenghao; Chen, Bo; Song, Xiaoguo; Li, Liqun
Graphical abstract: Highlights: Al/steel were successfully joined by laser welding-brazing technology. Interfacial microstructure and tensile strength of joints were evaluated. Thermodynamics was employed to clarify the diffusion behavior of Zn element. Abstract: Laser welding–brazing Al/steel with different Zn–Al filler metals was performed. Experiments and thermodynamics calculations were conducted to analyze microstructure evolution and elemental diffusion behavior, respectively. The interfacial intermetallic compounds (IMC) was composed of dominating layered η–Fe2 Al5 Zn0.4 phase and two different types of δ–FeZn10 phase. Scattered δ–FeZn10 phase among layered η–Fe2 Al5 Zn0.4 matrix was found in all joints while continuous δ–phase adjacent to steel substrate appeared in joint obtained with Zn–Al2 and Zn–Al15 fillers and disappeared in the case of Zn–Al22 filler. Thermodynamics calculation showed that Zn element preferentially diffused to the Fe–Al interface and steel substrate, and reacted with generated Fe–Al IMC and residual Fe elements, leading to the presence of Zn element in η–Fe2 Al5 Zn0.4 phase and the formation of δ–FeZn10 phase. The increasing Al addition in filler metals induced a more sufficient Fe–Al reaction, causing a thicker Fe–Al IMC layer and insufficient residual Fe elements at the interface. It would be harder for the Zn elements to diffuse through the η–Fe2 Al5 Zn0.4 layer with larger thickness. A higher Gibbs free energy of δ–FeZn10 phase compared with η–Fe2 Al5 Zn0.4 phase, insufficient Fe and Zn elements at the interface were all responsible for the disappearance of continuous δ–FeZn10 phase. Joint with the highest tensile strength was produced with Zn–Al22 filler owing to the disappearance of continuous δ–FeZn10 phase and crack–inhibitation effect of scattered δ–FeZn10 phase among layered Fe2 Al5 Zn0.4 matrix.